The Gospel of Matthew: Reconfigured Torah - Hays, Richard B. (HTS teologiese studies, 2005)
This essay surveys the evangelist Matthew’s reading of Israel’s Scripture. Rather than focusing only on Matthew’s distinctive formula quotations, we must observe the subtler ways that Matthew evokes scriptural images and patterns. The essay highlights four major aspects of Matthew’s reading of Scripture. (1) Matthew reads Israel’s Scripture as a story that highlights election, kingship, exile, and messianic salvation as the end of exile. (2) Matthew reconfigures Torah into a call for radical transformation of the heart. (3) Matthew highlights Scripture’s call for mercy, particularly by emphasizing Hosea 6:6 as the hermeneutical key to Torah. (4) Matthew interprets the mission to the Gentiles as the fulfilment of Israel’s destiny and the active embodiment of the authority of the Son of Man (Dn 7:13-14) over the whole world. Jointly taken, these strategies of interpretation produce a striking reconfiguration of Israel’s Torah.